Depletion of TrkB Receptors From Adult Serotonergic Neurons Increases Brain Serotonin Levels, Enhances Energy Metabolism and Impairs Learning and Memory - Sahu, Madhusmita P.; Pazos-Boubeta, Yago; Steinzeig, Anna; Kaurinkoski, Katja; Palmisano, Michela; Borowecki, Olgierd; Piepponen, Timo Petteri; Castrén, Eero (Frontiers in Molecular Neuroscience, 2021)
Neurotrophin brain-derived neurotrophic factor (BDNF) and neurotransmitter serotonin (5-HT) regulate each other and have been implicated in several neuronal mechanisms, including neuroplasticity. We have investigated the effects of BDNF on serotonergic neurons by deleting BDNF receptor TrkB from serotonergic neurons in the adult brain. The transgenic mice show increased 5-HT and Tph2 levels with abnormal behavioral phenotype. In spite of increased food intake, the transgenic mice are significantly leaner than their wild-type littermates, which may be due to increased metabolic activity. Consistent with increased 5-HT, the proliferation of hippocampal progenitors is significantly increased, however, long-term survival of newborn cells is unchanged. Our data indicate that BDNF-TrkB signaling regulates the functional phenotype of 5-HT with long-term behavioral consequences.